Limitations of Focused Assessment with Sonography for Trauma in Pelvic Trauma: A Retrospective Review of False-Positive Results and Non-Therapeutic Laparotomies - Pankaj Kumar; Swastik Sourav Mishra; Mantu Jain; Sujit Tripathy; Kasthala Sanjay Raj; Siddharth Satyakam Pradhan (Journal of Orthopaedic Case Reports)
Introduction: Focused assessment with sonography for trauma (FAST) is an important adjunct for quickly detecting intra-abdominal hemorrhage. The study was aimed to identify the incidence of non-therapeutic laparotomies with positive FAST result and pelvic fracture. Materials and Methods: A retrospective review of prospectively maintained data was conducted to identify cases of pelvic fracture with positive FAST results. Cases with non-therapeutic laparotomies were analyzed for the cause of false FAST positive result. The data were collected and analyzed for the mechanism of injury, associated injuries and injury severity. Results: Out of 195 cases of pelvic fracture with positive FAST result, only 5 cases (2.5%) had non-therapeutic laparotomies. Most were operated without a computed tomography scan due to hemodynamic instability. One patient was operated in view of peritonitis. Most common type of the injury requiring operative intervention was a vertical shear fracture. One patient was managed with an immediate external fixator, while three underwent a definitive pelvis fixation at a later date. One patient was managed conservatively. Conclusion: FAST has a high sensitivity for intra-abdominal bleeding. However, retroperitoneal hematoma in pelvic fractures can lead to false-positive FAST results. Therefore, we advocate for a comprehensive approach encompassing clinical judgment, additional imaging for stable patients, the engagement of a multidisciplinary team, and surgical expertise to ensure optimal patient care and outcomes.